Significance of Hematological Scoring System in Early Diagnosis of Neonatal Sepsis at a Tertiary Care Hospital - Chotaliya, Ankita Dineshbhai; Parikh, Nisarg; Patel, Falguni; Sheth, Nidhi (Annals of Pathology and Laboratory Medicine, 2024)
Background: Sepsis is the leading cause of death in neonates, accounting for 30%–50% of deaths in developing countries. Early diagnosis of neonatal sepsis remains challenging due to the nonspecific nature of its clinical features. While blood culture is the gold standard for diagnosis, it is time-consuming, taking several days, and can be costly. The Hematological Scoring System (HSS) is an alternative method that utilizes hematologic parameters—such as leukocyte count, polymorphonuclear (PMN) cells, immature PMN count, degenerative changes, and platelet count—for the early diagnosis of neonatal sepsis. Objectives: To determine the significance of the Hematological Scoring System (HSS) for the early detection of neonatal sepsis. Materials and Methods: This retrospective study enrolled 50 neonates admitted to the NICU at SMS Multi-Speciality Hospital, Chandkheda, Ahmedabad, who were clinically suspected of sepsis. Hematological parameters were measured for all subjects, and each case was analyzed using the HSS. Results: Among the 50 neonates in this study, the incidence of septicemia was 56% in males and 44% in females. Furthermore, 28% of neonates had an HSS greater than 5. Conclusion: HSS is a highly sensitive indicator of sepsis. Its use in peripheral smear studies can serve as an effective sepsis screening tool for early diagnosis, thereby helping to reduce neonatal morbidity and mortality.